An Overview on the Internet in the Learning Context - Ciptaningrum, Dyah Setyowati (Journal of English and Education (JEE), 2007)
The Internet might have been manypeople's best friends but there are also people who are still in the introduction stage of using the Internet. The Internet might become hype for them that they are not aware yet of the potentials and the harms lurking behind the glitters of the Internet. Thus, this paper is meant to provide general information on both the positive and negative side of the Internet in terms of educational context.Worshipping the Internet or having a skeptical position toward the Internet is two extremes that should be avoided. The Internet users should be critical and wise in using this piece of technology. In other words, they need to become 'informed' users of the Internet. Therefore, some possible solutions are also presented in this paper in order to make the best use of its potentials while focusing every effort to minimize its harms.